Cognitive and artificial intelligence system for logistics industry. (30th April 2020) - Zhao, Jing; Xie, Fengjie
Artificial intelligence is an important branch of cognitive science. Artificial intelligence has been applied to medical, education, logistics and other industries, which has broad prospects for development. Hotel logistics industry uses artificial intelligence technology to complete intelligent search, face recognition, combined with large data calculation and planning reasonable path in warehousing. Taking China's hotel logistics industry as the research object, this paper analyses the application of artificial intelligence technology in the logistics industry. In the warehousing process, artificial intelligence technologies including compile storage code, automatic picking with automated guided vehicle, warehouse robot to improve work efficiency. Logistics distribution links use artificial intelligence technology to plan the best path, improve the recognition rate of express waybill that save a lot of labour. Artificial intelligence technology allocates logistics resources, optimises logistics links, and improves logistics efficiency and other measures to promote the development of logistics informatisation and automation.